Endometrial cancer after pelvic radiotherapy: a case-report and review of literature - Passos Silva, Sara; Martins Miranda, Andreia; Gonçalves, Elisabete; Carvalho, Sónia; Simas, Ana; Carvalho, Agostinho (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Cancer treatment has evolved with advances in radiation and chemotherapy. However, over time the effects of ionizing radiation become more evident. In spite of attempting a more targeted therapeutic approach, the harmful effects of radiation on healthy tissues are many times inevitable. We report the case of a young woman who underwent chemoradiotherapy for stage IB2 cervical cancer with no evidence of relapse during 10 years follow-up. Instead she had radiation associated colitis and cystitis and vertebral necrosis. After 10 years an endometrial cancer was diagnosed. Radiation associated endometrial cancer is rare and may present with atypical symptoms making the diagnosis challenging. High degree of suspicion is necessary for an on time diagnosis and treatment.